Methodological framework to integrate social and physical vulnerability in the prevention of seismic risk - Izquierdo-Horna L. (2018)
This project was partially funded by CONCYTEC, within the framework of the 232-2015-FONDECYT Agreement. The authors would like to thank Joshua Wolfe for his valuable comments on the previous version of this manuscript.